GingaSpace - a solution to execute multidevice applications on broadband TV systems - Guedes, Álan L.V.; Costa, Luís F.S.; Guimarães, Ana P.N.; Vilarouca Filho, José I.; Brito, Fernando S. M.; Batista, Carlos E.C.F.; Souza Filho, Guido L (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2013: Proceedings of the 19th Brazilian Symposium on Multimedia and the Web, 2013)
Advances in interactive digital TV have enabled the introduction of application scenarios that explore Internet content and multiple device interaction. However, the authorship and interoperability for such scenarios is hampered by the diversity of technologies and devices involved. This paper presents a software architecture for a portable application store based on the H.761 ITU recommendation for IPTV services. The application store concept is implemented as a Ginga-NCL application, which retrieves and executes other Ginga-NCL applications. The description of the proposed software architecture, the execution of systems and usability tests on a software prototype are presented as results.